Isolation and characterization of cellulose from rice husk waste and sawdust with chemical method - RIZKI ANDALIA; RAHMI RAHMI; JULINAWATI JULINAWATI; HIRA HELWATI (Universitas Syiah Kuala, 2020)
Cellulose had been isolated from rice husk waste and sawdust with chemical method through hydrolysis with HCl 2.5 N and bleaching process with H2O23%.The yields were 13,45% and 22,75% (w/w) of cellulose from rice husk waste and sawdust, respectively. The chemical treatment caused partial removal of lignin and hemicellulose from raw material showed by FTIR spectrum. Structure and morphology of cellulose from rice husk waste and sawdust were investigated using X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The XRD patterns showed cellulose structure converted from amorphous to crystalline form after bleaching process while SEM images showed that the isolated cellulose from rice husk waste had rougher surface than cellulose from sawdust. The SEM micrograph also showed that the isolated cellulose from rice husk was in the form of aggregates.